Lean Six Sigma: Literature Review and Implementation for Textile and Textile Product (TTP) Industries - Kurnia, Hibarkah; Tumanggor, Ojakma Sihar Panaili; Jaqin, Choesnul (Proceeding Mercu Buana Conference on Industrial Engineering, 2021)
The Textile and Textile Product (TTP) industry starts from the preparation of fibers to become yarn rolls (Spinning Mills), fabrics (Weaving and Knitting), and Garments (Garments). There is a defect or production process waste in the process, so it needs continuous analysis and improvement to produce high productivity and improve quality by applying the Lean Six Sigma (LSS) method. However, research in the textile industry does not all use LSS. Some companies still use other ways, for example, Plan-Do-Check-Action (PDCA) and Quality Control Seven tools. This literature review aims to collect systematically from several studies, especially in the TTP sector, and to explain in the existing literature and identify the segments that produce the most publications. This research work is obtained from Google Scholar, Elsevier, Science Direct, and other publications in the world. This paper is based on a study of 30 LSS Sigma articles published from 2013 to 2020 in the world's leading journals. Journal collection is based on the textile industry segment and based on the country of origin of the journal publisher and year of publication. This literature review shows that 46% of journals are from the Garment segment, 40% of journals are from Indonesia, and in 2019, most publications